Eikôs-lógos kósmos philosophía - Escobar Moncada, Jairo Iván (Estudios de Filosofía, 1996)
The concept eikôs-lógos is central to Timaeus. In this essay it is intended to demonstrate that this concept summarizes Platos previous considerations on lógos. It can be said basically that it is inhered to lógos lato sensu a moment of image, and that platonic dialectics is achivied within the tension between image and concept. Therefore, the eikôs-lógos is characteristic not only of cosmology but, mainly, of philosophy. Eikôs points out the finite, terrestrial dimension of the philosophical lógos. The article concludes remarking that the roots of eikôs-lógos are language and number, which participare as well in the images we conceive of cosmos.